Congenital Anterior Urethral Diverticulum in a Male Teenager: A Case Report and Review of the Literature - Sadat Haider Quoraishi; Faisal Khan; Dler Besarani; Krishna Patil (Case Reports in Urology)
We present the case of a 13-year-old boy with a congenital anterior urethral diverticulum. This is a rare condition in males which can lead to obstructive lower urinary tract symptoms and urosepsis. Diagnosis is by urethroscopy and radiological imaging. Surgical treatment can be open or endoscopic. Long-term followup is required to check for reoccurrence of the obstruction.